DARI MEMORIA PASSIONIS KE FORERI: SEJARAH POLITIK PAPUA 1999-2000 - Suryawan, I Ngurah (Paramita: Historical Studies Journal, 2012)
This paper focuses on Papua memory of suffering in the tragedies of violations against humanity (memoria passionis) under the authority of the Indonesian Government with brutal military actions. Memoria Passionis was also a foundation of social movement in the urban people of Papua in 1999-2000. FORERI (Forum Rekonsiliasi Rakyat Irian Jaya Ã¢â‚¬â€œ Forum of the Irian Jaya PeopleÃ¢â‚¬â„¢s Reconciliation) and PDP (Presidium Dewan Papua- Papuan Presidium Council) were educated local elites who struggled for Papua freedom peacefully. FORERI then transformed into Tim 100 who met President Habibie in February 1999 with the claim that the people of Papua wanted independence (separation) from Indonesia. They carry out MUBES (Great Council) of Papuan people on 23 to 26 February 2000 and the Papuan Congress II from May to June 2000. Consolidation of democracy and social movement in Papua ended after Theys Hiyo Eluay, one of the leaders of PDP was killed by Indonesian Army in 2001. Keywords: Papuan, memoria passionis, social movement, local elites Ã‚Â  Makalah ini berfokus pada memori Papua orang tentang penderitaan dalam tragedi pelanggaran terhadap kemanusiaan (Memoria Passionis) di bawah kewenangan Pemerintah Indonesia dengan tindakan militer yang brutal. Memoria Passionis juga adalah dasar dari gerakan sosial di masyarakat perkotaan Papua pada 1999-2000. FORERI (Forum Rekonsiliasi Rakyat Irian Jaya) dan PDP (Presidium Dewan Papua) merupakan elite berpendidikan lokal berjuang kebebasan Papua dengan damai. FORERI kemudian bertransformasi menjadi Tim 100 yang bertemu Presiden Habibie pada Februari 1999 dengan tuntutan bahwa rakyat Papua menuintut kemerdekaan (memisahkan diri) dari Indonesia. Mereka melaksanakan MUBES (Musyawarah Besar) Rakyat Papua 23-26 Februari 2000 dan Kongres Rakyat Papua II Mei-Juni 2000. Konsolidasi demokrasi dan gerakan sosial di Papua berakhir setelah Theys Hiyo Eluay, salah satu pemimpin dari PDP dibunuh oleh Angkatan Darat Indonesia pada tahun 2001. Kata Kunci: Papua, memoria passionis, gerakan sosial, elite lokal. Ã‚Â